Kualitas Pelayanan Pajak Kendaraan Bermotor (PKB) di Kantor Manunggal Satu Atap (SAMSAT) Kabupaten Sikka - Meliani Vinsensa Dwiputri Liman; Melkisedek N.B.C. Neolaka; Aspri Budi Oktavianto (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to determine and analyze the quality of motor vehicle tax services at the Sikka Regency One-Stop Single Administration System (SAMSAT) office. This research is a qualitative research with data collection techniques namely observation, interview and documentation. The informants in this study were the community and the SAMSAT office. The results of this study reveal that motor vehicle tax services at the Sikka Regency SAMSAT Office are classified as good, but not yet fully optimized. The tangible dimension shows that physical facilities are adequate, although there are still shortcomings in infrastructure and comfort of the waiting room. From the reliability aspect, the service is considered satisfactory and efficient, but the application of the SOP still needs to be improved. In the responsiveness dimension, officers show good responsiveness, but the delivery of information to taxpayers still needs to be improved. Meanwhile, the assurance dimension shows professionalism and efficiency in service time, although the friendly attitude of officers has not been evenly distributed. Finally, from the empathy aspect, SAMSAT's commitment to bring services closer to the community through various innovations is seen, but the awareness of taxpayers in fulfilling their obligations still varies. Thus, improvements are needed in physical aspects, consistency of SOPs, and information dissemination so that services become more qualified and in accordance with community expectations.